Assessment of the magnitude of geographical variations and socioeconomic contextual effects on ischaemic heart disease mortality: a multilevel survival analysis of a large Swedish cohort. Issue 4 (19th March 2007) - Chaix, Basile; Rosvall, Maria; Merlo, Juan
Abstract : Background: In a public health perspective, it is of interest to assess the magnitude of geographical variations in ischaemic heart disease (IHD) mortality and quantify the strength of contextual effects on IHD. Objective: To investigate whether area effects vary according to the individual and contextual characteristics of the population, socioeconomic contextual influences were assessed in different age groups and within territories of differing population densities. Design: Multilevel survival analysis of a 28-year longitudinal database. Participants: 341 048 residents of the Scania region in Sweden, reaching age 50–79 years in 1996, followed up over 7 years. Results: After adjustment for several individual socioeconomic indicators over the adult age, Cox multilevel models indicated geographical variations in IHD mortality and socioeconomic contextual effects on the mortality risk. However, the magnitude of geographical variations and strength of contextual effects were modified by the age of individuals and the population density of their residential area: socioeconomic contextual effects were much stronger among non-elderly than among elderly adults, and much larger within urban territories than within rural ones. As a consequence, among non-elderly residents of urban territories, the socioeconomic contextual effect was almost as large as the effect of individual 20-year cumulated income. Conclusions: Non-elderly residents of deprived urban neighbourhoods constitute a major target for both contextual epidemiology of coronary disease and public health interventions aimed at reducing the detrimental effects of the social environment on IHD.